Production of Highly Uniform Midbrain Organoids from Human Pluripotent Stem Cells - Xuerui Yao; Ji Hyun Kang; Kee-Pyo Kim; Hyogeun Shin; Zhe-Long Jin; Hao Guo; Yong-Nan Xu; Ying-Hua Li; Sai Hali; Jeongwoo Kwon; Hyeonwoo La; Chanhyeok Park; et al. (Stem Cells International)
Brain organoids have been considered as an advanced platform for in vitro disease modeling and drug screening, but numerous roadblocks exist, such as lack of large-scale production technology and lengthy protocols with multiple manipulation steps, impeding the industrial translation of brain organoid technology. Here, we describe the high-speed and large-scale production of midbrain organoids using a high-throughput screening-compatible platform within 30 days. Micro midbrain organoids (µMOs) exhibit a highly uniform morphology and gene expression pattern with minimal variability. Notably, µMOs show dramatically accelerated maturation, resulting in the generation of functional µMOs within only 30 days of differentiation. Furthermore, individual µMOs display highly consistent responsiveness to neurotoxin, suggesting their usefulness as an in vitro high-throughput drug toxicity screening platform. Collectively, our data indicate that µMO technology could represent an advanced and robust platform for in vitro disease modeling and drug screening for human neuronal diseases.